A Survey for the Spectrum of Triangles over Sequence Spaces. (10th December 2019) - Yeşilkayagil, Medine; Başar, Feyzi
Abstract: In the present paper, we summarize the recent literature concerning the spectrum and fine spectrum with respect to Goldberg's classification of some operators represented by an infinite matrix over certain sequence spaces.